(untitled) (Revista Brasileira Multidisciplinar, 2025)
The study aims to analyze the profile of users of a General CAPS in a city in northeastern Brazil in the context of the pandemic by COVID-1.This is a descriptive, cross-sectional and documental study, with a quali-quantitative approach. The population was made up of users of the institution and health professionals from the Psychosocial Care Center type II of Quixadá. The results obtained reveal the predominance of female users, being in 2019 (55.5%) of the open medical records, and in 2020 (59.6%).The predominant age group is 30 to 59 years. As for the marital status and educational level of users, the survey identified a higher prevalence of singles and people with incomplete elementary education. In a pandemic year (2020) there was an increase in anxiety disorders, showing a 2.2% increase compared to 2019, as well as the report of feelings of fear that had an increase of (6.2%). Also in the year 2020, 22 users cited the pandemic as the determining factor for triggering their symptoms. Other variants were on the rise such as suicidal ideation (2.5%), and attempted suicide (0.9%) compared to 2019.